Independent service operators in ATM markets - Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This paper studies the impact of entry of non-banks (termed Independent Service Operators, ISOs) into ATM markets. We compare two different regimes by which the ISO may generate income: i) The ISO receives interchange fees and ii) the ISO charges consumers directly. We find that due to the entry of an ISO the size of the total ATM network increases independent of the way the ISO is financed. Account fees increase if the ISO receives interchange fees and decrease if the ISO charges consumers directly. Consumers may not benefit from the entry of the ISO. If a regulator can control the interchange fee, entry by an ISO financed through interchange fees increases consumer surplus, while the entry of a surcharging ISO decreases consumer surplus.
Keywords: L11; L13; 330; Banking; ATM networks; Investment